Investigation of Factors Influencing EFL Students’ Satisfaction in Online Learning: A Literature Review - Santosa, Made Hery; Yasa, I Gede Bayu Kartika (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
The rapid transition to online learning, accelerated by the global pandemic, has significantly influenced students' satisfaction with their educational experiences, particularly among English as a Foreign Language (EFL) learners. This literature review aims to synthesize key themes related to EFL students' satisfaction in online learning environments. Employing a systematic literature review methodology, nine empirical studies were investigated based on rigorous inclusion criteria, ensuring a comprehensive analysis of the topic. Thematic analysis was utilized to identify and interpret emerging themes from the selected studies. The findings indicate that EFL students' satisfaction is shaped by six critical factors, namely facilities, flexibility, interaction, instructor quality, learning outcomes, and the overall learning environment. Each of these factors plays a pivotal role in enhancing or detracting from the online learning experience. The discussion highlights the interconnectedness of these elements, suggesting that a holistic approach is necessary for improving student satisfaction in the online learning context. Educational institutions and instructors must prioritize these factors to optimize online learning experiences. The results highlights the importance of adapting teaching methodologies to meet the evolving needs of EFL students in a digital landscape. Future research should explore the long-term implications of these findings, particularly in developing innovative strategies that foster engagement and satisfaction in online learning contexts. By addressing these areas, stakeholders can significantly enhance the quality of online education, ensuring it remains effective and responsive to student needs in the post-pandemic era.